An adaptive metastructure concept using bistable composite laminates - Kumar A.; Haldar A.; Weaver P.M. (My University, 2025)
Concepts involving adaptive and morphing structures offer us the possibility to realise shape transformation with each shape imparting an individual functionality. There is an increased demand in the design of structural components that are suitable for diverse operational conditions rather than limited to a unique one. However, most concepts of shape adaptive structures require a “holding force” or a continuous supply of energy to maintain a targeted 3D shape. As a result, structures that can lead to desired shape transformation with self-locking capabilities are more desirable. In this work, the concept of multistability is employed to demonstrate a novel class of metastructures that can tackle this challenge. The metastructure is constructed with a periodic arrangement of bistable unit cells made of highly anisotropic composite laminates. Each unit cell comprises multi-sectioned rectangular composite plates exhibiting bistable behaviour due to the thermal residual stresses engendered during the cool-down process from curing to room temperature. To analyse the proposed metastructure, a finite element model has been developed at three hierarchical levels: a plate level, a unit cell level, and a lattice level. At the plate level, a corresponding semi-analytical model using the Rayleigh–Ritz method has also been formulated to validate the finite element models. By carefully tuning the size and spacing of the unit cell, a desired response of the metastructure can be achieved. Additionally, by changing the ply layup and the fibre orientation of each layer of constituent composite plates, conflicting requirements, including load-carrying, shape-adaptive and lightweight, at the same time can be addressed simultaneously. From an extensive parametric study, few designs have been selected for its application in a load-carrying morphing structure. © 2023